SEJARAH KERAJAAN PADANG DI KOTA TEBING TINGGI SUMATERA UTARA DI BAWAH KEKUASAAN RAJA JAMTA MELAYU (1806-1853) - Siti Ardiantari; Isjoni Isjoni; Bunari Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: the purpose of this study is (1) to find out the history of the emergence of the kingdom of padang (2) To know the glory of the kingdom under the rule of the king of malay(3) To know the decline of the kingdom of the field (4) To find out the relics of the kingdom of the field. The benefit of this research are (1) To applicatiom the science of the writer Selma sitting on the lecture bench, adding to the write’s insight into local history (2)To obtain a bachelor’s degree in education science at the University of Riau (3) as a reference source for readers, the government and the people of North Sumatera, especially the people in the City Tebing Tinggi about the history of the kingdom of Padanf in order to complete local historical writing (4) as a scientific work contribution to the history education program of Riau University (5) As a means of information and reference material for further research related to the same problem, especially for history students. In this method uses qualitative research methods. The results of this study, the kingdom that once stood at jln. K.F Tandean the 3 main city neighboarhoods of the Tebing Tinggi North Sumatera around the 17 th century. During the heyday of the Padang Kingdom around 1806, during the reign of king Jamta Malay can be seen from various aspects, such as government, social, economic, culture, and religion. The period of decline or the collapse of the padang kingdom around 1946 during the reign of Tengku Hasyim. The factors that led to the collapse of the Padang kingdom were caused by a number of.Key Words : History, The kingdom of the field of Padang